PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL, RISIKO LITIGASI, LIKUIDITAS, DAN POLITICAL COST TERHADAP KONSERVATISME AKUNTANSI - Azwir Nasir '; Elfi Ilham '; Yusniati ' ' (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
This study aims to determine the effect of structure manajerial, litigation risk, liquidity, and political cost on accounting conservatism at 2011 and 2012 years. This study use purposive sampling method to choose the sample, so there are 34 (thirty four) sample company. The method of analysis used in this study is descriptive quantity method, simultaneous regression test and partial test (multiple regression analysis using SPSS version 17.0). Simultaneous regrression test (F test) showed that the independent variables studied simultaneously have a significant effect on the dependent variable. Partial regression test showed that the liquidity variable has the significant effect to the conservatism. The magnitude of the effect that (R2) by the four independent variables together against the dependent variables 22 %, while the remaining 78 % is influenced by other variables not examined in this study.Kata Kunci : Accounting consevatism, structure manajerial, litigation risk, liquidity, political cost